2001
DOI: 10.1093/bja/86.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone is a cost-effective alternative to ondansetron in preventing PONV after paediatric strabismus repair

Abstract: This study evaluated the antiemetic efficacy, cost-effectiveness and clinical utility of prophylactic ondansetron and dexamethasone compared with placebo in the prevention of postoperative nausea and vomiting (PONV) in 135 children (2-15 yr, ASA I-II) undergoing strabismus repair. After induction with halothane and nitrous oxide in oxygen or i.v. thiopental, the children received i.v. dexamethasone 1 mg kg(-1) to a maximum of 25 mg, ondansetron 100 microg kg(-1) to a maximum of 4 mg or placebo (n=45). Episodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 27 publications
4
54
0
1
Order By: Relevance
“…13,19 Since a dose of 2.5 or 5 mg were found to be equally effective as 10mg in reducing the incidence of postoperative emesis in patients undergoing major gynaecological surgeries, a dose of 4 mg was chosen in this study. 13 Our study has shown that prophylactic use of 4 mg dexamethasone intravenously 1 hour prior to SAB, in patients undergoing TAH, significantly reduces the incidence of nausea and vomiting and the requirement of antiemetics in the postoperative period.…”
Section: -11mentioning
confidence: 99%
“…13,19 Since a dose of 2.5 or 5 mg were found to be equally effective as 10mg in reducing the incidence of postoperative emesis in patients undergoing major gynaecological surgeries, a dose of 4 mg was chosen in this study. 13 Our study has shown that prophylactic use of 4 mg dexamethasone intravenously 1 hour prior to SAB, in patients undergoing TAH, significantly reduces the incidence of nausea and vomiting and the requirement of antiemetics in the postoperative period.…”
Section: -11mentioning
confidence: 99%
“…Dexamethasone is a glucocorticoid that produces a strong antiemetic effect 16,17 by an undetermined mechanism. It may act through prostaglandin antagonism, 18 serotonin inhibition in the gut, 19 and by releasing endorphins.…”
Section: Objectif : La Combinaison De Médicaments Antiémétiques Pourrmentioning
confidence: 99%
“…Recently, a combination of ondansetron and dexamethasone has been shown to be a highly effective prophylactic measure in patients undergoing laparoscopic cholecystectomy [6]. However, the higher cost of ondansetron has been a significant factor limiting its routine prophylactic use [28]. Therefore, we used metoclopramide, the most common and low-cost antiemetic agent, instead of ondansetron.…”
mentioning
confidence: 99%